Cytotoxic alkaloids from the root of Zanthoxylum paracanthum (mildbr) Kokwaro. Issue 10 (23rd May 2022) - Omosa, Leonidah Kerubo; Nchiozem-Ngnitedem, Vaderament-A; Mukavi, Justus; Atieno Okoko, Brenda; Ombui Nyaboke, Helder; Hashim, Ibrahim; Obegi Matundura, Jackson; Efferth, Thomas; Spiteller, Michael
Abstract: Chemical investigation of the root of Zanthoxylum paracanthum afforded 1 new alkamide derivative, (2 E, 4 E )-6-oxo- N -isobutyldeca-2, 4-dienamide (1 ) together with 10 known congeners including one phenolic amide (2 ), four benzophenanthridines (3 − 6 ), three indolonaphthyridines (7 − 9 ) and two lignans (10 and 11 ). Their structures were elucidated by a combination of spectroscopic and spectrometric data. Using resazurin reduction assay, the crude extract (10 µg/mL) and isolates (10 µM) were screened for their cytotoxic activities against the drug-sensitive (CCRF-CEM) leukemia cell line and its multidrug-resistant counterpart (CEM/ADR5000). Compounds 3, 4 and 6 showed cytotoxicity against CCRF-CEM with IC50 values of 2.00 ± 0.33, 2.31 ± 0.20 and 0.11 ± 0.04 µM, respectively. Only compound 6 exhibited strong cytotoxic activity against CEM/ADR5000 with an IC50 value of 2.34 ± 0.34 µM in comparison with the standard drug doxorubicin which showed IC50 values of 0.01 ± 0.14 (CCRF-CEM) and 26.78 ± 3.30 µM (CEM/ADR5000). Graphical Abstract: UF0001